1969
DOI: 10.1039/j39690001821
|View full text |Cite
|
Sign up to set email alerts
|

α-Aminoacyl derivatives of aminobenzoic acid and of amino-oxy-acids by reaction of their hydrochlorides with amino-acid N-carboxyanhydrides

Abstract: The reaction of amino-acid N-carboxyanhydrides with hydrochlorides of aminobenzoic acids and of aminooxy-acids gave amino-acid amides in a one-step synthesis. The coupling of L-alanine N-carboxyanhydride with anthranilic and with p-aminobenzoic acid hydrochloride gave peptide-like compounds of high optical activity. indicating the presence of little or no racemate. Glycyl and DL-phenylalanyl amides with aminobenzoic acid were obtained in this way, and trimers were formed by reaction of the N-carboxyanhydrides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
2
14
0
1
Order By: Relevance
“…The modified amino acids were then converted to their corresponding NCA monomers to allow subsequent polymerization. CD analysis of the water-soluble polymer in deionized water at pH 7 revealed that it was in a disordered chain conformation [35,36]. The CD spectra of this polymer were also invariant with solution pH and buffer strength, consistent with this result.…”
Section: Side-chain-functionalized Polypeptidessupporting
confidence: 87%
See 2 more Smart Citations
“…The modified amino acids were then converted to their corresponding NCA monomers to allow subsequent polymerization. CD analysis of the water-soluble polymer in deionized water at pH 7 revealed that it was in a disordered chain conformation [35,36]. The CD spectra of this polymer were also invariant with solution pH and buffer strength, consistent with this result.…”
Section: Side-chain-functionalized Polypeptidessupporting
confidence: 87%
“…Their strategy was to avoid formation of NCA anions, which cause significant chain termination after rearranging to isocyanocarboxylates [11,12], through use of primary amine hydrochloride salts as initiators. The reactivity of amine hydrochlorides with NCAs was first explored by the group of Knobler, who found that they could react hydrochlorides with NCAs to give single NCA addition products [35,36]. Use of the hydrochloride salt takes advantage of its diminished reactivity as a nucleophile compared to the parent amine, which effectively halts the reaction after a single NCA insertion by formation of an inert amine hydrochloride in the product.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to inhibit side reactions such as the activatedmonomer mechanism, [25] the PDMAMNH 2 macroiniator was converted to the corresponding ammonium salt (PDMAMNH þ 3 Cl À ) following a procedure reported in the literature. [17,30,[34][35][36][37] Subsequently, the PDMAMNH þ 3 Cl À chains were employed as the macroinitiator for the ROP of NCA-TFALL [6,10,12,13,25,29] resulting in the PDMAM x -block-PTFALL y diblock copolymers. The PDMAMNH 2 block length was kept constant in all cases, whereas the PTFALL length was varied systematically with the y values being equal to 10, 23, 42 and 98.…”
Section: Polymerization Methodologymentioning
confidence: 99%
“…Chemistry Synthesis of the reported intermediates; I [27], II [28], III and IV [29], VIa [30], VIb [31], VIIa [32], VIIb [33], VIIc [34], VIId [32],VIIe [35], VIIIb, IXb [36], XIa, XIb [37], XIc [38], XId and XIe [39], XIIa [40], XIIb [41], XIIc [42], XIId [43], XIIe [44], XIIIa [45], XIIIb [46], XIVa [46], XIVb [47], XIVc [48], XIVd [49] and XIVe [50] were performed according to the corresponding reported procedures outlined in Schemes 1-3. The new intermediates (VIIIa, c, d, e) were prepared by a similar method for preparing VIIIb [37], by hydrocyanation of the appropriate substituted cinamoylacetanilides (VIIa, c-e) by acetone cyanohydrin.…”
Section: Resultsmentioning
confidence: 99%